Elephant and rhino population trends in Selous, Tanzania - Iain Douglas-Hamilton (Pachyderm)
The first aerial surveys of the Selous Game Reserve were undertaken in the wet and the dry seasons of 1976. Later counts were made in 1979 along the Rufiji River, and in 1981 in the north-east Selous. All counts used the same method of counting and analysis. The results between 1976 and 1979 in the Rufiji area of 14,417 to 10,081 gave a 30% decrease for elephants and estimates of 571 down to 290 gave a 49% decrease for rhinos. In north-east Selous between 1976 and 1981 the elephants estimate from 29,026 to 22,589 was 22% lower showing a slight decrease but the rhinos decreased drastically from 1173 to 298 which is approximately 75%.